POPOKAN, TRADISI PERANG LUMPUR Tradisi Desa Sendang, Kecamatan Bringin, Kabupaten Semarang - Muh Hafidz (Sabda: Jurnal Kajian Kebudayaan, 2017)
Initially the tradition of popokan is the original tradition of Sendang village. It is developed into a unique tradition in Semarang Regency. The tradition is not only limited to the tradition of mud war among villagers of Sendang Village, but also modified with various processions in the form of cleaning wells or water sources, tumpengan (food offering), carnival and popokan war. Popokan tradition is an expression of gratitude to God the Almighty as the Ruler of the Universe, in order to keep away from various disasters and calamities. This tradition is also an expression of artistic ability and creativity of citizens, especially after the Tourism Office of Semarang Regency manages it in order to preserve local wisdom from the tradition of the local ancestors.